Dimensionally and morphologically controlled growth of calcium phosphate crystals by an organic-free hydrothermal process. Issue 15 (15th November 2016) - Li, Ruijing; Cai, Yurong; Yang, Ying; Fang, Shunbin; Su, Xiuping; Sun, Yunqing; Yao, Juming
Abstract: Calcium phosphate (CaP) materials are optimal candidate biomaterials for bone tissue engineering because of their bioactivity and biocompatibility. The controlled fabrication of CaP materials draws great interest because the size, shape and composition of CaP crystals play critical roles in biological response. In this study, CaP nanowires and microspheres were synthesised via an organic-free hydrothermal process without the assistance of any surfactant or template. The effect of the reaction condition on CaP crystal growth was investigated. Experimental results showed that the size, shape and composition of the obtained CaP crystals could be manipulated by changing nucleation temperature, reaction temperature, pH value and reaction time. The chemical composition of the obtained crystals had a common change process from dicalcium phosphate dihydrate and dicalcium phosphate anhydrous to hydroxyapatite with the elongation of reaction time. The prenucleation and nucleation temperature before hydrothermal treatment were critical for the growth of CaP crystal. Two typical morphologies of nanowire and microsphere were fabricated under the given reaction condition. The growth mechanisms of the crystals were also discussed in this paper. In vitro results showed that both nanowires and microspheres of CaP exhibited exceptional performance to improve osteoblast proliferation, which endowed them with interesting potential for bone repair. The findings are highly important to develop excellent materials suitable for bone tissue engineering.